Nigeria Digital Economy Diagnostic Report - World Bank Group (World Bank, Washington, DC, 2019)
As the biggest economy in Africa with one of the largest youth populations in the world, Nigeria is well-positioned to develop a strong digital economy. This would have a transformational impact on the country. In order to reap the benefits, Nigeria needs to focus on accelerating improvements in five fundamental pillars of a digital economy: digital infrastructure, digital platforms, digital financial services, digital entrepreneurship and digital skills. The Nigeria Digital Economy Diagnostic report identifies key challenges and opportunities of leveraging the digital economy for diversified and sustained growth. It provides an assessment of the state of Nigeria’s digital economy around the five foundational pillars. The report also offers specific, actionable recommendations to the government and private sector stakeholders to further Nigeria’s development of each pillar. The report was produced in the context of the Digital Economy (DE4A) initiative, an African Union initiative supported by the World Bank Group, which aims to digitally connect every person, business, and government in Africa by 2030.